The Effect of Tax Avoidance, Profitability, and Leverage on Firm Value - Nailufaroh, Lulu (ADPEBI, 2022)
This study aims to determine the Effect of Tax Avoidance, Profitability, and Leverage on Firm Value in Manufacturing Companies in the Goods and Consumer Sector Listed on the Indonesia Stock Exchange for the period 2016 – 2019. This type of research is Causal Associative research with a Quantitative approach. The sample in this study was determined using the purposive sampling method and obtained from as many as 24 companies. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that profitability affects firm value. Meanwhile, tax avoidance and leverage have no effect on firm value.